eHealth Literacy Interventions for Older Adults: A Systematic Review of the Literature - Watkins, Ivan; Xie, Bo (JMIR Publications, 2014)
BackgroundeHealth resources offer new opportunities for older adults to access health information online, connect with others with shared health interests, and manage their health. However, older adults often lack sufficient eHealth literacy to maximize their benefit from these resources. ObjectiveThis review evaluates the research design, methods, and findings of eHealth literacy interventions for older adults. MethodsA systematic review of peer-reviewed research articles from 28 databases in 9 fields was carried out in January 2013. Four rounds of screening of articles in these databases resulted in a final sample of 23 articles. ResultsFindings indicated a significant gap in the literature for eHealth literacy interventions evaluating health outcomes as the outcome of interest, a lack of theory-based interventions, and few studies applied high-quality research design. ConclusionsOur findings emphasize the need for researchers to develop and assess theory-based interventions applying high-quality research design in eHealth literacy interventions targeting the older population.